USE OF SENSOR STICK MEDIA TO IMPROVE MOBILITY ORIENTATION SKILLS IN TUNANETRA CHILDREN IN SAMANTHA SKH - Haifa Nurul Ghassani; Ratih Listiyangtyas; Reza Febri Abadi; Nurkolisa Plb; riska Apriliya; Yeyet Yuliyanti (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2019)
Use of Sensor Stick Media to improve mobility orientation capabilities to make it easier for children to do activities at school or outside school. In this study so that the media is well arranged used assessment in order to find out the media that is suitable with the needs of children both in academic and non-academic terms. The purpose of this study was to help children improve mobility orientation skills by using a sensor stick on blind children in SKh X in Serang City. The method used is a quantitative method with a type of experimental research. The targets in this study are 1) facilitating daily activities and 2) making it easy to move without the help of others. Based on the results of the study, it is known that the sensor stick can improve the orientation and mobility capabilities of blind children in SKh X in Serang City.